Early detection and integrated care for adolescents and young adults with psychotic disorders: the ACCESS III study. (6th June 2017) - Lambert, M.; Schöttle, D.; Ruppelt, F.; Rohenkohl, A.; Sengutta, M.; Luedecke, D.; Nawara, L. A.; Galling, B.; Falk, A.‐L.; Wittmann, L.; Niehaus, V.; Sarikaya, G.; et al.
Abstract : Objective: The objective of the study was to investigate whether a combined intervention composed of early detection plus integrated care (EDIC) enhances outcomes in patients with early psychosis compared to standard care (SC). Methods: ACCESS III is a prospective non‐randomized historical control design 1‐year study examining the efficacy of EDIC ( n = 120) vs. SC ( n = 105) in patients aged 12–29 years. Primary outcome was the rate of ≥6 months combined symptomatic and functional remission. Additional outcomes comprised the reduction of DUP and course of psychopathology, functioning, quality of life, and satisfaction with care. Results: In observed cases, 48.9% in the EDIC and 15.2% in the SC group reached the primary endpoint. Remission was predicted by EDIC (OR = 6.8, CI: 3.15–14.53, P < 0.001); younger age predicted non‐remission (OR = 1.1, CI: 1.01–1.19, P = 0.038). Linear regressions indicated a reduction of DUP in EDIC ( P < 0.001), but not in SC ( P = 0.41). MMRMs showed significantly larger improvements in PANSS positive ( P < 0.001) and GAF ( P < 0.01) scores in EDIC vs. SC, and in EDIC over time in CGI‐Severity ( P < 0.001) and numerically in Q‐LES‐Q‐18 ( P = 0.052). Conclusions: EDIC lead to significantly higher proportions of patients achieving combined remission. Moderating variables included a reduction of DUP and EDIC, offering psychotherapeutic interventions.